Emotional Experiences of Women After Stillbirth: A Qualitative Study from Turkey. - Güvenç , Gülten; Kök, Gülşah; Özgen, Hatice Nur; Bulgurcu, Rahime Aksoy; Ertuğrul, Merve (Bangladesh Journal of Medical Science, 2025)
Background Stillbirth is an extremely traumatic and distressing experience with serious negative effects for the woman, her partner and family. Stillbirth has lasting emotional, cognitive, social, psychological and physiological consequences on families that are often underestimated. This study aims to determine the emotional experiences of women who had stillbirth. Method Phenomenological approach, one of the qualitative research designs, was adopted in the study. The study was conducted between January-June 2021 in a training and research hospital in Ankara, Turkey. Data were obtained through Personal Data Collection Form and Semi-structured Interview Form. The descriptive Colaizzi method was employed to analyse the qualitative data. This study was reported according to the Consolidated Criteria for Reporting Qualitative Research checklist. Results In the study, 12 women were interviewed, and their emotional states were analysed under five main themes. These are the emotions experienced when the pregnancy was first learned, the effects of bereavement due to stillbirth, the attitude towards the baby after stillbirth, the factors influencing the bereavement process and the methods of coping with the bereavement process. Conclusion Stillbirth is an important phenomenon that deeply influences the lives of women. Therefore, it is crucial to address the psychosocial aspects of the process in the care of stillbirth mothers. BJMS, Vol. 24 No. 03 July’25 Page : 825-836